Development and Trial of Interactive Ebook Based on SQ3R Strategy to Improve Elementary School Students' Reading Comprehension Skills - Rakhmawati, Sari; Wibowo, Setiawan Edi; Hamdi, Zul Fadli (Journal of Innovation and Research in Primary Education, 2025)
This study aims to develop and test the effectiveness of an interactive e-book based on the SQ3R (Survey, Question, Read, Recite, Review) strategy to improve elementary students’ reading comprehension skills. The research employed a Research and Development (R&D) approach adapted from Borg and Gall’s model, consisting of seven stages: potential and problem identification, data collection, product design, expert validation, product revision, limited trials, and field testing. The product’s validity and practicality were evaluated by media experts, content experts, and elementary teachers. The participants involved one classroom teacher and 30 fifth-grade students from a public elementary school in Sleman, Yogyakarta, Indonesia. Data were collected using expert validation sheets, student response questionnaires, and reading comprehension tests. The results indicated that the developed e-book was categorized as “very valid” (89.6%), “practical” according to teachers and students, and “effective” in improving reading comprehension, as shown by a significant increase in post-test scores. The findings demonstrate that integrating the SQ3R strategy into an interactive e-book is a valid, practical, and effective medium for enhancing students’ comprehension skills. Future studies are recommended to extend this digital tool into mobile or web-based learning platforms.